2020
DOI: 10.1002/jum.15447
|View full text |Cite
|
Sign up to set email alerts
|

Role of Point‐of‐Care Lung and Inferior Vena Cava Ultrasound in Clinical Decisions for Patients Presenting to the Emergency Department With Symptoms of Acute Decompensated Heart Failure

Abstract: Objectives This prospective study was performed to evaluate the diagnostic role of point‐of‐care lung ultrasound (LUS) and inferior vena cava (IVC) ultrasound in patients with acute decompensated heart failure (ADHF). Methods A prospective cohort study was conducted between January 2018 and November 2018 on patients with a diagnosis of ADHF in the emergency department (ED). On admission, LUS findings, inspiratory and expiratory IVC diameters, and the inferior vena cava collapsibility index (IVCCI) were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…These reference variables included clinical assessment of volume status change (based on the resolution of peripheral edema) following administration or adjustment of diuretic dose as well as comparison to volume status determined from physical examination and reference echocardiography measurements. While most studies assessed the correlation between POCUS and the reference variables, Tchernodrinski et al and Hacıalioğulları et al assessed the change in IVC diameter relative to baseline at various time points following diuretic administration 14 , 15 .The reliability of POCUS as a tool compared to other methods of assessing volume status was tested by Nixon et al and Dalen et al Nixon et al found a significant correlation between physical volume assessment and POCUS IVC d measurements 13 , and Dalen et al found a significant correlation between POCUS and baseline echocardiography measurements of IVC max , IVC min , and determination of PE 16 .…”
Section: Resultsmentioning
confidence: 99%
“…These reference variables included clinical assessment of volume status change (based on the resolution of peripheral edema) following administration or adjustment of diuretic dose as well as comparison to volume status determined from physical examination and reference echocardiography measurements. While most studies assessed the correlation between POCUS and the reference variables, Tchernodrinski et al and Hacıalioğulları et al assessed the change in IVC diameter relative to baseline at various time points following diuretic administration 14 , 15 .The reliability of POCUS as a tool compared to other methods of assessing volume status was tested by Nixon et al and Dalen et al Nixon et al found a significant correlation between physical volume assessment and POCUS IVC d measurements 13 , and Dalen et al found a significant correlation between POCUS and baseline echocardiography measurements of IVC max , IVC min , and determination of PE 16 .…”
Section: Resultsmentioning
confidence: 99%
“…Another study [31] demonstrated cardiac ultrasound may identify an unanticipated critical finding in sepsis patient. Moreover, B-line artifacts finding appeared to represent the left ventricular function and volume status of the patient [32] , [33] . However, the accuracy of POCUS diagnosed in distributive shocked patient was only 69.61 % which the agreement of with the final hospital diagnosis was fair.…”
Section: Discussionmentioning
confidence: 96%
“…A number of small, randomized trials have evaluated the utility of POCUS as a tool for improving efficiency and accuracy of diagnosis of a variety of intrathoracic conditions including respiratory failure and cardiopulmonary congestion from HF, the results of which have been in favor of its use [60][61][62][63]. There is some evidence to suggest that demonstration of pulmonary B-lines on POCUS and measurement of inferior vena cava (IVC) diameters may outperform traditional objective measures of volume assessment including NT-ProBNP level and CXR findings [64,65]. Expert opinion currently supports the use of POCUS as an augmentation to comprehensive volume status examination, which has been supported by consensus statements and recommendations by the American Society of Echocardiography and the American College of Physicians [66,67].…”
Section: Imagingmentioning
confidence: 99%